Happy dose stimulating the neurochemicals of happiness of the Bukang Liwayway Minimum Security Camp Inmates through a therapeutic landscape design - Mojica, Vielle Michaela J.; Dul-loog, Vic L. (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
People constantly try to pursue happiness. It is one of the goals in life. Biologically, certain neurochemicals can also be stimulated in order to feel happiness namely dopamine, oxytocin, serotonin, and endorphins. Though there are many different ways to achieve happiness, in the midst of stress and hardships, happiness may be hard to reach. For the incarcerated, prison is a constant everyday struggle with stress. They cannot make choices on their own, they have no control over the things they can do and their surroundings, and their privacy is taken away. In addition to poor prison conditions, prisoners suffer physical, mental, and emotional stress which does not aid in their process of rehabilitation. The proposed landscape design of the "Happy DOSE: stimulating the neurochemicals of happiness of the Bukang Liwayway Minimum Security Camp Inmates through a therapeutic landscape design" aims to help promote the health and well-being of the inmates and help in their goal of rehabilitation and reintegration to society with the use of a therapeutic landscape incorporated with activities and conditions stimulating the neurochemicals of happiness. Through data gathered from related literature, questionnaires for the inmates, and interviews with the staff, spaces needed in the site were established.
Include appendices.
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Prisons -- Design and construction; Prisoners -- Mental health services